Community-based family companions empowerment for People with Mental Disorders (PWMD) in Bandarharjo Village, Semarang - Rochmawati, Dwi Heppy; Susanto, Wigyo; Ellyawati, Hetty Catur (Community Empowerment, 2021)
Community empowerment is an effort to provide power or strengthening to the community. Bandarharjo Village, Semarang has 54 people with mental disorders. As many as 75% have received treatment. Among those who have received treatment, 50% of people with mental disorders regularly control and take medication. Therefore, it takes the participation of the family as well as the community known as the mental health cadres to pay attention to this mental health problem. Activities were carried out using the nursing process method which includes assessment, planning, action and evaluation. This service has succeeded in forming mental health cadres in Bandarharjo Village. In addition, the cadres have also been given orientation so that they are expected to be able to carry out their role well in handling people with mental disorders.